Biomechanical Effects of Prefabricated Foot Orthoses and Rocker‐Sole Footwear in Individuals With First Metatarsophalangeal Joint Osteoarthritis. Issue 5 (May 2016) - Menz, Hylton B.; Auhl, Maria; Tan, Jade M.; Levinger, Pazit; Roddy, Edward; Munteanu, Shannon E.
Abstract : Objective: To evaluate the effects of prefabricated foot orthoses and rocker‐sole footwear on spatiotemporal parameters, hip and knee kinematics, and plantar pressures in people with first metatarsophalangeal (MTP) joint osteoarthritis (OA). Methods . A total of 102 people with first MTP joint OA were randomly allocated to receive prefabricated foot orthoses or rocker‐sole footwear. The immediate biomechanical effects of the interventions (compared to usual footwear) were examined using a wearable sensor motion analysis system and an in‐shoe plantar pressure measurement system. Results: Spatiotemporal/kinematic and plantar pressure data were available from 88 and 87 participants, respectively. The orthoses had minimal effect on spatiotemporal or kinematic parameters, while the rocker‐sole footwear resulted in reduced cadence, percentage of the gait cycle spent in stance phase, and sagittal plane hip range of motion. The orthoses increased peak pressure under the midfoot and lesser toes. Both interventions significantly reduced peak pressure under the first MTP joint, and the rocker‐sole shoes also reduced peak pressure under the second through fifth MTP joints and heel. When the effects of the orthoses and rocker‐sole shoes were directly compared, there was no difference in peak pressure under the hallux, first MTP joint, or heel; however, the rocker‐sole shoes exhibited lower peak pressure under the lesser toes, second through fifth MTP joints, and midfoot. Conclusion: Prefabricated foot orthoses and rocker‐sole footwear are effective at reducing peak pressure under the first MTP joint in people with first MTP joint OA, but achieve this through different mechanisms. Further research is required to determine whether these biomechanical changes result in improvements in symptoms.